2004
DOI: 10.1111/j.1365-2249.2004.02534.x
|View full text |Cite
|
Sign up to set email alerts
|

Osteoprotegerin (OPG) acts as an endogenous decoy receptor in tumour necrosis factor-related apoptosis-inducing ligand (TRAIL)-mediated apoptosis of fibroblast-like synovial cells

Abstract: SUMMARYWe examined the role of osteoprotegerin (OPG) on tumour necrosis factor-related apoptosis-inducing ligand (TRAIL)-induced apoptosis in rheumatoid fibroblast-like synovial cells (FLS). OPG protein concentrations in synovial fluid from patients with rheumatoid arthritis (RA) correlated with those of interleukin (IL)-1 b or IL-6. A similar correlation was present between IL-1 b and IL-6 concentrations. Rheumatoid FLS in vitro expressed both death domain-containing receptors [death receptor 4 (DR4) and DR5]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
59
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(61 citation statements)
references
References 28 publications
2
59
0
Order By: Relevance
“…This decoy receptor for TRAIL could have a clear role in the modulation of TRAIL resistance because it has been proposed to be involved in the resistance of tumor cells to TRAIL. 85,86 Inflammation can boost the host responses to the tumor and somehow change the tumor microenvironment for enhanced antigen presentation and tissue access. 87 Thus, a recent report suggests that not a lack of tumoricidal activity of T cells but rather the failure of T cells to infiltrate the tumor tissue may prevent tumor rejection.…”
Section: Influence Of the Tumor Microenvironment On Trail-induced Apomentioning
confidence: 99%
“…This decoy receptor for TRAIL could have a clear role in the modulation of TRAIL resistance because it has been proposed to be involved in the resistance of tumor cells to TRAIL. 85,86 Inflammation can boost the host responses to the tumor and somehow change the tumor microenvironment for enhanced antigen presentation and tissue access. 87 Thus, a recent report suggests that not a lack of tumoricidal activity of T cells but rather the failure of T cells to infiltrate the tumor tissue may prevent tumor rejection.…”
Section: Influence Of the Tumor Microenvironment On Trail-induced Apomentioning
confidence: 99%
“…We previously reported apoptosis (Kawakami et al 1999Miyashita et al 2003Miyashita et al , 2004Tamai et al 2006), cell differentiation ), cell proliferation (Eguchi et al 1992;Migita et al 2000Migita et al , 2001, signal transduction (Yamasaki et al , 2002, sensitivity to drugs , and protein expression of the rheumatoid synovial cells Tanaka et al 2004) using the long-time cultured synovial cells derived from the knee joint replacement surgery. As the cell population and the expression of TNF receptors both dramatically changed in the synovial cells derived from both surgery and a synovectomy after long-term cultures (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…TRAILR3 and TRAILR4 are considered as membrane neutralizing or regulatory receptors. Although OPG has been initially identified as a member of the soluble tumor necrosis factor (TNF)-receptor family, inhibiting RANKLmediated osteoclastogenesis, several in vitro studies have shown its ability to also neutralize TRAIL (Emery et al 1998, Miyashita et al 2004). …”
Section: Introductionmentioning
confidence: 99%